Diagnostic Approach to Neonatal Hypotonia - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2008)
The frequency of various disorders causing neonatal hypotonia and the reliability of the first physical examination and standard diagnostic tests were evaluated by a retrospective review of records of 144 patients diagnosed between 1999 and 2005 at Strasbourg University Hospital, France.